The Nef-Like Effect of Murine Leukemia Virus Glycosylated Gag on HIV-1 Infectivity Is Mediated by Its Cytoplasmic Domain and Depends on the AP-2 Adaptor Complex - Usami, Yoshiko (American Society for Microbiology, 2014)
Human immunodeficiency virus type 1 (HIV-1) Nef enhances the infectivity of progeny virions. However, Nef is dispensable for the production of HIV-1 virions of optimal infectivity if the producer cells are superinfected with certain gammaretroviruses. In the case of the ecotropic Moloney murine leukemia virus (M-MLV), the Nef-like effect is mediated by the glycosylated Gag (glycoGag) protein. We now show that the N-terminal intracellular domain of the type II transmembrane protein glycoGag is responsible for its effect on HIV-1 infectivity. In the context of a fully active minimal M-MLV glycoGag construct, truncations of the cytoplasmic domain led to a near total loss of activity. Furthermore, the cytoplasmic domain of M-MLV glycoGag was fully sufficient to transfer the activity to an unrelated type II transmembrane protein. Although the intracellular region of glycoGag is relatively poorly conserved even among ecotropic and xenotropic MLVs, it was also fully sufficient for the rescue of nef-deficient HIV-1 when derived from a xenotropic virus. A mutagenic analysis showed that only a core region of the intracellular domain that exhibits at least some conservation between murine and feline leukemia viruses is crucial for activity. In particular, a conserved YXXL motif in the center of this core region was critical. In addition, expression of the μ2 subunit of the AP-2 adaptor complex in virus producer cells was essential for activity. We conclude that the ability to enhance HIV-1 infectivity is a conserved property of the MLV glycoGag cytoplasmic domain and involves AP-2-mediated endocytosis. IMPORTANCE The Nef protein of HIV-1 and the entirely unrelated glycosylated Gag (glycoGag) protein of a murine leukemia virus (MLV) similarly enhance the infectiousness of HIV-1 particles by an unknown mechanism. MLV glycoGag is an alternative version of the structural viral Gag protein with an extra upstream region that provides a cytosolic domain and a plasma membrane anchor. We now show for the first time that the cytosolic domain of MLV glycoGag contains all the information needed to enhance HIV-1 infectivity and that this function of the cytosolic domain is conserved despite limited sequence conservation. Within the cytosolic domain, a motif that resembles a cellular sorting signal is critical for activity. Furthermore, the enhancement of HIV-1 infectivity depends on an endocytic cellular protein that is known to interact with such sorting signals. Together, our findings implicate the endocytic machinery in the enhancement of HIV-1 infectivity by MLV glycoGag.